Generalized Fuzzy Rough Approximations on Hypergroups - Canan Akın; Dilek Bayrak Delice; Sultan Yamak (Mathematics, 2024)
In this paper, we define the fuzzy set-valued homomorphisms of the canonical hypergroups as a generalization of fuzzy congruences and investigate some of their features. This structure is an extension of the definition of set-valued homomorphism defined for groups to hypergroups. With this extension, it has become possible to study generalized fuzzy rough approximations in hyperalgebraic structures such as semihypergroups, polygroups, hyperrings, hypermodules, etc. This paper presents the generalized fuzzy rough approximations based on two-universe <semantics>(I,T)</semantics>-fuzzy model on canonical hypergroups.